AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN WRITING RECOUNT TEXT AT THE TENTH GRADE STUDENTS - Hasugian, Nova Kalsim; Silitonga, Harpen; Lestari, Febrika Dwi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
This study analyses students' grammatical errors in writing recount texts among tenth-grade students at SMK Swasta Jambi Medan. Writing is an important skill in English that requires the use of proper grammar to convey ideas effectively. However, many students have difficulties with grammatical structures, which affect the clarity and coherence of their writing. This study aims to identify and classify the types of grammatical errors found in students' recount texts and determine the most dominant types of errors.This study used a qualitative descriptive method, with data collected from students' writing test. Errors were analyzed using Dulay's Taxonomy of Surface Strategies, which categorizes errors into omission, addition, misformation errors, and misordering errors. The findings showed that misformation errors were the most frequent (76.59%), followed by addition errors (14.89%), omission errors (8.51%), and misordering errors (0%). The prevalence of tense errors shows that students struggle mainly with the use of verb tenses, irregular verb tenses, and subject-descriptor congruence.The results of this study highlight the need for improved grammar teaching, especially in verb and sentence structure. Teachers should focus on strengthening grammar rules through targeted practice, while curriculum developers can use these findings to design more effective English writing programs. By addressing these common errors, students can improve their writing accuracy and overall language proficiency.